Multi-Locus Typing of Histomonas meleagridis Isolates Demonstrates the Existence of Two Different Genotypes - Bilic, Ivana (Public Library of Science, 2014)
Histomonas meleagridis is the aetiological agent of histomonosis or “blackhead disease”. Histomonosis is of special importance today, because there is no effective treatment to prevent its occurrence with considerable losses for the poultry industry. Despite its importance only a few molecular studies have yet been performed to investigate the degree of genetic diversity between different isolates of this parasite. In the present study a collection of well defined samples, previously shown positive for the DNA of H. meleagridis, was used to investigate genetic relatedness of the parasite. Samples originated from 25 turkey flocks collected in France between 2007 and 2010. Additionally, diagnostic samples, collected at our Clinic in Vienna, from different European countries and Azerbaijan, during 2010 to 2013 were included in the analyses. For the analysis three different genetic loci were analyzed: 18S rRNA, α-actinin1 and rpb1 genes. To amplify partial sequences of α-actinin1 and rpb1 genes, primers specifically targeting H. meleagridis were designed. Following PCR, the sequences of 18S rRNA, α-actinin1 and rpb1 loci were analyzed. Phylogenetic analyses demonstrated separation of H. meleagridis isolates in two different clusters. The majority of isolates grouped within the cluster 1 and originated from different European countries. The cluster 2 was rare and predominantly found in samples originating from France. Considering that the genetic variability of clusters can be seen as two distinct genetic types we propose the term genotype instead of cluster.